AEROSOL GENERATION MODES FOR NICOTINECONTAINING PRODUCTS - M. V. Shkidyuk; S. V. Kalashnikov; I. A. Reznichenko (Новые технологии)
Nicotine-containing products (NCP) are innovative products containing nicotine, including heated tobacco and liquids for electronic nicotine delivery systems. NCP consumption using nicotine delivery systems (NDS) occurs by inhaling the aerosol generated by heating tobacco/tobacco filler or nicotine-containing liquids.Considering nicotine-containing products as an alternative to traditional smoking determines the need to study the component composition of the generated aerosol. The quantitative determination of the toxic components of nicotine-containing products and the aerosol produced is carried out in many scientific and production laboratories. The monitoring of world studies that are potentially applicable to determine the priority toxic components in the NCP aerosol.The development of an integrated methodology for sample preparation (generation, collection of aerosol components) and instrumental determination of toxic compounds of NCP aerosol is an urgent task in terms of assessing product risks.The article presents the results of studies conducted in the Laboratory of the technology for tobacco production of the FSBSI RSRITTI on the choice of aerosol generation modes for testing NCPs of various designs on a Cerulean SM 405 smoking machine.As a result of the research, a technique has been developed for machine generation of aerosol to determine the toxicity level of NCPs based on the content of carbonyl compounds and nitrosoamines.